2022
DOI: 10.1051/epjconf/202227408011
|View full text |Cite
|
Sign up to set email alerts
|

Unitarizing infinite-range forces: Graviton-graviton scattering, the graviball, and Coulomb scattering

Abstract: We study graviton-graviton scattering in partial-wave amplitudes after unitarizing their Born terms. In order to apply S -matrix techniques, based on unitarity and analyticity, we introduce an S -matrix associated to this resummation that is free of infrared divergences. This is achieved by removing the diverging phase factor calculated by Weinberg that multiplies the S matrix, and that stems from the virtual infrared gravitons. A scalar graviton-graviton resonance with vacuum quantum numbers is obtained as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Starting from the tree level amplitude the authors of [20][21][22][23] found a pole in the J = 0 channel at s 0 = πxM 2 p ≈ (0.22 − i0.63)M 2 P with x = 0.07 − i0.2 which they claim is a pure gravitational resonance (graviball). This particular x value corresponds to some arbitrary but reasonable choice of an UV cut-off Λ which is needed for their unitarization method (in fact the position of the pole depends logarithmically on Λ).…”
Section: Discussionmentioning
confidence: 99%
“…Starting from the tree level amplitude the authors of [20][21][22][23] found a pole in the J = 0 channel at s 0 = πxM 2 p ≈ (0.22 − i0.63)M 2 P with x = 0.07 − i0.2 which they claim is a pure gravitational resonance (graviball). This particular x value corresponds to some arbitrary but reasonable choice of an UV cut-off Λ which is needed for their unitarization method (in fact the position of the pole depends logarithmically on Λ).…”
Section: Discussionmentioning
confidence: 99%